2021
DOI: 10.1017/s136898002100197x
|View full text |Cite
|
Sign up to set email alerts
|

Pattern analysis of vegan eating reveals healthy and unhealthy patterns within the vegan diet

Abstract: Objective: This study aimed to identify the types of foods that constitute a vegan diet and establish patterns within the diet. Dietary pattern analysis, a key instrument for exploring the correlation between health and disease was used to identify patterns within the vegan diet. Design: A modified version of the EPIC-Norfolk food frequency questionnaire (FFQ) was created and validated to include vegan foods and launched on social media. Setting: UK participants, recrui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 47 publications
5
26
0
1
Order By: Relevance
“…In fact, most of the available PBMAs are manufactured in the form of sausages, burgers or nuggets and contain higher amounts of sodium, oil and additives, including coloring, flavoring and binding agents, in comparison to unprocessed meats [ 19 , 20 ]. Several studies have shown that the avoidance of animal-based food appears to be associated with the introduction of ultra-processed PBMAs over more natural plant sources, compromising the general quality of a plant-based diet [ 21 , 22 , 23 ]. Moreover, ultra-processed food has been associated with several health problems, like overweight and obesity, as well as metabolic syndrome prevalence, LDL cholesterol, risk of hypertension, and higher risks of cardiovascular, coronary heart, and cerebrovascular diseases [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, most of the available PBMAs are manufactured in the form of sausages, burgers or nuggets and contain higher amounts of sodium, oil and additives, including coloring, flavoring and binding agents, in comparison to unprocessed meats [ 19 , 20 ]. Several studies have shown that the avoidance of animal-based food appears to be associated with the introduction of ultra-processed PBMAs over more natural plant sources, compromising the general quality of a plant-based diet [ 21 , 22 , 23 ]. Moreover, ultra-processed food has been associated with several health problems, like overweight and obesity, as well as metabolic syndrome prevalence, LDL cholesterol, risk of hypertension, and higher risks of cardiovascular, coronary heart, and cerebrovascular diseases [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrate the proposed method in a case study regarding the finding of substitute products for a diet plan in the context of vegan products. The idea relies on the use of different ingredients in preparations that mimic animal products commonly results in similar products from the sensory point of view, but divergent with regard to nutritional composition [14]. In this situation, suppose, for instance, a diet plan consisting of the categories pork, fish and poultry.…”
Section: Case Studymentioning
confidence: 99%
“…(9) . Greater food availability and choice has permitted a larger number of dietary patterns to be followed within the standard definitions of vegan and vegetarian (9) . Following the publication of our review many new studies have examined iodine in the diet of vegans and vegetarians.…”
Section: Introductionmentioning
confidence: 99%